Higher Education EFL Teachers’ Code-switching Practices: Patterns and Functions in Focus - Gebrewahid Tsige Gerezgiher; Hailom Banteyerga Amaha (IAIN Syekh Nurjati Cirebon, 2024)
This study was conducted to investigate higher education EFL teachers’ code-switching patterns and functions. To achieve this objective, data was gathered through classroom observation audio record and semi-structured interview. A total of 24 lessons of 2400 minutes were recorded, and six teachers participated in the interview. The results obtained show that the teachers’ CS frequency increased as the students’ grade level that they were teaching increased. Besides, it was found that teachers of all grade levels employed inter-sentential CS more dominantly. Finally, the results obtained indicate that teachers of all class years were CS for curriculum access purposes more dominantly. Based on the findings, it is concluded that the different patterns of CS that the teachers were employing at the different grade levels have many functions in the EFL classes, and it helps the teaching and learning of English if it is handled properly. However, the teachers use of CS has to decrease as the students’ grade level goes up and the students’ EFL performance is improved. Teachers’ overuse of CS diminishes students’ exposure to the target language and their practice to English language in classes where English is a foreign language. Therefore, teachers’ CS patterns and functions should vary depending on their students’ grade level. In short, teachers should re-evaluate their CS practices and employ it depending up on their students’ CS desire and grade level.